2018
DOI: 10.1111/tpj.14083
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid‐specific prenyltransferase gene family in soybean: GmPT01, a pterocarpan 2‐dimethylallyltransferase involved in glyceollin biosynthesis

Abstract: Phytoalexin glyceollins are soybean-specific antimicrobial compounds that are derived from the isoflavonoid pathway. They are synthesized by soybean in response to extrinsic stress such as pathogen attack or injury, thereby conferring partial resistance if synthesized rapidly at the site of infection and at the required concentration. Soybean produces multiple forms of glyceollins that result from the differential prenylation reaction catalyzed by prenyltransferases (PTs) on either the C-2 or C-4 carbon of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 59 publications
(89 reference statements)
0
39
0
Order By: Relevance
“…Plants can defend against multiple biotic factors by the constitutive and inducible defense mechanisms [1][2][3]. The inducible defenses encompass various strategies, such as the promoted biosynthesis of phytoalexins [28][29][30][31], the enhanced activities of enzymes involved in the biosynthesis of antimicrobial compounds [32][33][34], and the increased expression of pathogenesis-related (PR) proteins [35][36][37][38]. Phytoalexins have been identified as important antimicrobial metabolites for plant defense against pathogens and pests [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Plants can defend against multiple biotic factors by the constitutive and inducible defense mechanisms [1][2][3]. The inducible defenses encompass various strategies, such as the promoted biosynthesis of phytoalexins [28][29][30][31], the enhanced activities of enzymes involved in the biosynthesis of antimicrobial compounds [32][33][34], and the increased expression of pathogenesis-related (PR) proteins [35][36][37][38]. Phytoalexins have been identified as important antimicrobial metabolites for plant defense against pathogens and pests [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Often, more than one type can be found in a single plant species and the same isoflavonoids may be produced by different plant species. In soybean, daidzein is metabolized to produce glyceollins, which serve as defense mechanisms against several, primarily fungal, pathogens [30]. In the model legume Medicago truncatula , formononetin is metabolized into medicarpin, a phytoalexin that is conncected with pathogen resistance [31].…”
Section: Isoflavone Role In Plantsmentioning
confidence: 99%
“…Molecular characterization of PT genes revealed that G4DT and G2DT are paralogs resulting from a whole-genome duplication (Yoneyama et al, 2016). A genome-wide analysis of PT genes in G. max Wm82 identified 77 PT-encoding genes with 11 putative isoflavonoid-specific PTs (Sukumaran et al, 2018). One of the candidate genes, GmPT01 (G2DT-2) was induced by P. sojae infection and AgNO 3, which mimics pathogen attack and lies in the QTL linked to P. sojae resistance.…”
Section: Defense-related Traitsmentioning
confidence: 99%